2021
DOI: 10.2196/29319
|View full text |Cite
|
Sign up to set email alerts
|

Association of Substance Use With Behavioral Adherence to Centers for Disease Control and Prevention Guidelines for COVID-19 Mitigation: Cross-sectional Web-Based Survey

Abstract: Background Substance use is a risk factor for COVID-19 infection and adverse outcomes. However, reasons for elevated risk for COVID-19 in substance users are not well understood. Objective The aim of this study was to evaluate whether alcohol or other drug use is associated with adherence to Centers for Disease Control and Prevention (CDC) guidelines for COVID-19 mitigation. Preregistered analyses tested the hypothesis that greater use of alcohol and other drugs would b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 37 publications
2
20
1
1
Order By: Relevance
“…This suggests that a binational policy response to COVID-19 is warranted beyond the closure of the U.S.-Mexico border. We did not observe substance use behaviors, such as smoking, vaping, or use of specific drugs such as opiates or stimulants to be associated with an elevated risk of SARS-CoV-2 infection, as others have hypothesized [9]. Instead, we observed that circumstances in the risk environment, notably sex work and incarceration, were independently associated with higher SARS-CoV-2 seroprevalence.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…This suggests that a binational policy response to COVID-19 is warranted beyond the closure of the U.S.-Mexico border. We did not observe substance use behaviors, such as smoking, vaping, or use of specific drugs such as opiates or stimulants to be associated with an elevated risk of SARS-CoV-2 infection, as others have hypothesized [9]. Instead, we observed that circumstances in the risk environment, notably sex work and incarceration, were independently associated with higher SARS-CoV-2 seroprevalence.…”
Section: Discussioncontrasting
confidence: 75%
“…In a telephone survey of active and former drug injectors in Baltimore, Maryland, compared to former substance users, those who were actively using substances were less likely to report social distancing, which could increase their risk of acquiring SARS-CoV-2 [ 7 ]. In an online survey of adults residing in the Northeastern U.S., daily users of opioids and alcohol were less likely to adhere to COVID-19 related stay-at-home orders, and stimulant users were more likely to report having tested positive for SARS-CoV-2 [ 9 ]. There are also reports that the COVID-19 pandemic has interrupted global drug supplies as well as harm reduction and addiction treatment services, which could alter drug use patterns [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…· Did you wear a mask if it is difficult to keep a distance of more than two meters between people outdoors? Li et al [ 31 ] Graupensperger et al [ 36 ] Monnig et al [ 37 ] Social distancing · Did you maintain a two-meter distance between people for your health? · Did you refrain from going outside/meetings/events?…”
Section: Methodsmentioning
confidence: 99%
“…COVID-19 preventive behaviors were based on the guidelines of World Health Organization, Centers for Disease Control and Prevention, and prior literature [ 31 , 36 , 37 ]. Three items are assessed with eight questions: hand washing, wearing a mask, and social distancing.…”
Section: Methodsmentioning
confidence: 99%
“…This study was a cross-sectional online survey administered to a sample recruited on Amazon’s Mechanical Turk (MTurk) platform by the Center for Addiction & Disease Risk Exacerbation (CADRE) at Brown University School of Public Health. Recruitment details for the baseline sample, collected from June 18 through July 19, 2020, have been described previously [ 22 ]. A follow-up survey was conducted in May 2021 for participants who completed the baseline survey with additional questions regarding COVID-19 vaccine hesitancy and beliefs regarding healthcare systems and practices.…”
Section: Methodsmentioning
confidence: 99%